Evaluation of choroidal structural changes after silicone oil removal in rhegmatogenous retinal detachment - Ozcaliskan, Sehnaz; Balci, Sevcan (Annals of Medical Research, 2021)
Aim: To evaluate the choroidal structural changes after silicone oil (SiO) removal in patients who underwent pars plana vitrectomy (PPV) for macula off rhegmatogenous retinal detachment (RRD).Material and Methods: In this retrospective study, the charts of patients with macula off RRD who underwent SiO removal between February and June 2019 were reviewed. The subfoveal choroidal thickness (SFCT) was measured before and after SiO removal by enhanced depth imaging optical coherence tomography (EDI OCT). The subfoveal choroidal area was (TCA) segmented into luminal (LA) and interstitial stromal area (SA) by the binarization technique using ImageJ software (Version 1.52i, National Institutes of Health, Bethesda, MD USA). Choroidal vascularity index (CVI) was defined as the ratio of LA to the TCA. Results: There were 15 (%62.5) male and 9 (%37.5) female patients in the study group. The mean SFCT was 288.71±63.63 µm under SiO in the operated eyes. After SiO removal the mean SFCT significantly decreased to 259.33±51.25 µm at month 3 (p=0.004). The mean CVI was 63.37±3.50% under SiO filled eyes. After SiO removal, the mean CVI significantly decreased to 58.83±3.41% at month 3 (p0.001). The mean LA was 1.37±0.46 vs. 1.18±0.47 preoperatively and postoperatively in the operated eyes (p=0.028). There was no significant difference in the mean SA and TCA values between preoperative and postoperative measurements (p=0.742, p=0.175, respectively). Conclusion: Image binarization of EDI OCT scans and CVI analysis enables the assessment of choroidal changes after SiO removal. CVI decreased and the lumens of the choroidal vessels became smaller after SiO removal. CVI may be used as a parameter to monitor the choroidal changes that might be associated with inflammation secondary to SiO.